SOUTH AMERICAN DENDROECOLOGICAL FIELDWEEK 2016: EXPLORING DENDROCHRONOLOGICAL RESEARCH IN NORTHERN PATAGONIA - Amoroso, Mariano M.; Speer, James H.; Daniels, Lori D.; Villalba, Ricardo; Cook, Edward; Stahle, David; Srur, Ana; Tardif, Jacques; Conciatori, France; Aciar, Eugenia; Arco, Julieta; Bonada, Anabela; et al. (My University, 2018)
The South American Dendroecological Fieldweek (SADEF) associated with the Third American Dendrochronology Conference was held in El Bolson, Argentina, in March 2016. The main objective of the SADEF was to teach the basics of dendrochronology while applying specific knowledge to selected research questions. The course included participants and instructors from six different countries. This report describes activities of the course and briefly summarizes exploratory group projects. The Introductory Group developed an Austrocedrus chilensis chronology from 1629-2015 and documented a persistent decline in growth since 1977 which supports the fact that the current severe drought is the most severe in the 386-year record. Based on regional A. chilensis chronologies from 32. to 39. S Latitude, the Stream Flow Reconstruction Group developed a regional 525 year-long reconstruction from Rio Chubut and found the most severe drought episodes from 1490 to the present occurred from 1680-1705, 18131828, 1900-1920, 1993-2002, and from 2011 to the present. The Drought Reconstruction Group used A. chilensis annual tree-ring width chronologies to develop preliminary spatial field reconstructions of the Palmer Drought Severity Index spanning the Central Andes region. The reconstructions explain up to 81% of the 1907-1975 PDSI variance, indicating this tree species is powerful for informing on historical drought especially in very arid domains. The Dendroecology Group documented three spreading fires since the 1850s with a 12-year return interval but lack of fire for the last 94 years; they also documented a persistent decline in their chronologies in recent years, dating back to 1965.
Keywords: fieldweek; south america; dendroclimatology; dendroecology; dendrochronology